MiR-126-5p Down-Regulation Alleviates the Inflammatory Response of Allergic Rhinitis in Children via Inhibiting HIPK2/NF-κB Signaling Pathway - Jing Y; Xie J; Long S; Huang M (Journal of Inflammation Research)
Yunlong Jing, Jiang Xie, Songliang Long, Min Huang Department of Otolaryngology Head and Neck Surgery, Hunan Children’s Hospital, Changsha, 410007, People’s Republic of ChinaCorrespondence: Min Huang, Department of Otolaryngology Head and Neck Surgery, Hunan Children’s Hospital, No. 86, Ziyuan Road, Changsha, 410007, People’s Republic of China, Tel +86-0731-85356311, Email huangmin2005dr@163.comPurpose: The objective of our study was to exploit the potential mechanism of microRNA-126-5p (miR-126-5p) in the occurrence and formation of allergic rhinitis (AR) in children.Patients and Methods: Nasal mucosal tissues were obtained from AR in children and patients with adenoidectomy. Human nasal epithelial cell line (RPMI-2650) and BALB/c mice models were, respectively, established via ovalbumin (OVA) stimulation. Target genes and proteins levels were determined through quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) assays. The interaction of miR-126-5p with homeodomain-interacting protein kinase 2 (HIPK2) was confirmed via dual-luciferase reporter detection.Results: MiR-126-5p was memorably increased in nasal mucosal tissue specimens of AR children compared with patients with adenoidectomy, while HIPK2 was distinctly declined (all P< 0.05). A negative association was found between miR-126-5p and HIPK2 expression (r=− 0.5757, P< 0.001). Moreover, HIPK2 was predicted to be targeted by miR-126-5p. Proinflammatory cytokines expressions were significantly increased, and anti-inflammatory cytokines were obviously decreased in AR RPMI-2650 cell model (P< 0.001). NF-κB signaling pathway was also activated in AR RPMI-2650 cell model. MiR-126-5p inhibitor mitigated the stimulated function by OVA. Silencing HIPK2 recused miR-126-5p inhibitor phenomena in AR RPMI-2650 cell model. Furthermore, in vivo experiments further verified in vitro results, documenting that miR-126-5p inhibitor and si-HIPK2 relieved AR in the mice model.Conclusion: MiR-126-5p down-regulation relieved inflammation response and events of AR in children and mice model of AR through HIPK2/NF-κB signaling pathway, suggesting being a latent therapeutic target in AR. Keywords: MiR-126-5p, HIPK2, NF-κB signaling pathway, allergic rhinitis